The sports medicine team: The role of the strength & conditioning specialist - Wathen, D. (coachesinfo.com, 2008)
About the role of the strength & conditioning specialist within the sports medicine team. The term Sports Medicine is widely used and has numerous meanings. Many feel that anyone who has anything to do with health education, illness and injury prevention, treatment and rehabilitation, and basic and applied research of active (sports and general fitness) populations is involved with Sports Medicine. Certainly within this broad context the Strength and Conditioning Specialist can be found. Generally these members of the Sports Medicine team work with healthy populations but they can also serve to supply the link between formal physiotherapy and return to active participation for injured athletes and fitness enthusiasts. Their main contribution to the athletic individual is improved performance however their main function to the Sports Medical team is in the area of injury prevention.